Mata Pelajaran PPKn Kd. 3.6/4.6 Materi Ancaman Terhadap Negara dan Upaya Penyelesaiannya di Bidang Ipoleksosbudhankam dalam Bingkai Bhinneka Tunggal Ika Melalui Model Project Based Learning Metode Focus Group Discussion Pada Kelas X.IPS.4 MAN 2 Kota Payak - Nora Delfianis (Journal on Education, 2022)
This study aims to see and analyze the improvement of student learning outcomes in Civics subjects 3.6/4.6 the topic of threats to the state and its resolution efforts in IPOLEKSOSBUDHANKAM within the framework of Bhinneka Tunggal Ika through a project-based learning model with focus group discussion method in Class X.IPS.4 MAN 2 Payakumbuh in the even semester of the 2021/2022 academic year. This research was conducted using the Classroom Action Research method which consisted of two cycles. The results obtained from this study were by using a project-based learning model, the focus group discussion method can improve character strengthening and student learning outcomes. This can be seen from the increase in learning outcomes. Strengthening student character can be improved. The implementation of this research was carried out in two cycles, the second cycle was used to complete the first cycle. The subjects of this study were 35 students who had a low average character, namely in the pre-cycle 69.80% classically and 67.86% individually, with category K. The conclusion obtained from this study was the use of project-based learning models with focus methods. group discussion can improve the character and student learning outcomes.